Understanding the impact of social media usage among organizations - Tajudeen, Farzana Parveen; Jaafar, Noor Ismawati; Ainin, Sulaiman (Elsevier, 2018)
This study investigates the antecedents and impact of social media usage in organizations. This study uses the technology, organization, and environment framework and includes certain antecedent factors that are specific to social media usage in organizations. The items to measure different purposes of social media usage in organizations were developed, which contribute to the enhancement of social media usage measurement. This study develops and tests an integrated model that contributes to the scholarly research on social media and information systems. The study also helps organizations to understand the benefits of social media usage and provides a justification for investments in social media by organizations.